A Comprehensive Leadership Response to an Unexpected Maternal Death. Issue 1 (June 2015) - Weir, Faye J.
<x xml:space="preserve">Abstract</x> Poster Presentation Purpose for the Program The purpose of this presentation is to describe the successful development and implementation of a leadership pathway for response to an unanticipated, maternal death during pregnancy. The pathway is comprehensive and addresses family support, staff support, risk management, regulatory notification, and media response planning for short term and long term periods and may be individualized to a specific institution and area of practice. Proposed Change Development of a leadership pathway that can be tailored to a variety of settings. Responses of leadership can vary after a catastrophic event therefore, the pathway will ensure that all areas for response and support are assessed and addressed as needed. Implementation, Outcomes, and Evaluation Implementation of the pathway is individualized and occurs after an unanticipated, catastrophic event (such as a maternal death) and is based on leadership and organizational need. The outcomes will demonstrate that all areas are assessed and appropriate action plans implemented. Evaluation of effectiveness of pathway will be done at the user level, whereby they may make additional modifications based on staff/family and colleague feedback. Implications for Nursing Practice In the published literature, leadership response in cases of unanticipated maternal death is limited to debriefing with staff. The literature does not address the comprehensive response plan or any type of guide/pathway that the user may implement/modify as necessary. Additional research regarding a comprehensive response program related to staff support is necessary.